Urban Tourism Governance in Bali: Integration of Waste Management and Cultural Preservation - Ni Gusti Putu Adi Murtini; Nyoman Diah Utari Dewi; Ni Putu Tirka Widanti (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
The rapid development of urban tourism in Bali has boosted economic growth, but has also triggered complex challenges such as waste issues and cultural heritage degradation. Waste management in Bali's urban tourism areas still faces structural challenges, ranging from limited infrastructure capacity, weak inter-agency coordination, to low participation by the community and tourism businesses. This study aims to analyze the role of public administration in managing urban tourism through soft tourism and slow tourism approaches as sustainable development strategies based on cultural preservation (heritage tourism). Using qualitative methods with literature review and policy analysis, this study examines regulations and collaborative practices between government, communities, and industry. The analysis is conducted within the theoretical framework of good governance, collaborative governance, and sustainable public management. The results indicate that strengthening collaborative-based governance improves waste management effectiveness and supports equitable tourism. From a good governance perspective, the principles of transparency, accountability, and public participation still need to be strengthened, particularly in waste management in urban tourism areas. Soft and slow tourism approaches have proven relevant as policy instruments for maintaining a balance between economic growth, environmental sustainability, and cultural heritage protection. This research recommends the importance of cross-sectoral policy integration and strengthening regional institutional capacity to achieve sustainable urban tourism governance. Keywords: Bali, Public Administration, Urban Tourism, Waste Management, Soft Tourism